2007
DOI: 10.1097/phm.0b013e31805bfff5
|View full text |Cite
|
Sign up to set email alerts
|

Inconsistent Knee Varus Moment Reduction Caused by a Lateral Wedge in Knee Osteoarthritis

Abstract: In approximately 18% of patients with bilateral medial compartment knee OA, the 6-degree lateral wedge seems to fail to reduce the knee-joint varus moment. The indication and limitations of lateral wedge should be confirmed by a randomized controlled study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
52
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 25 publications
7
52
2
Order By: Relevance
“…The variable stiffness shoe results are in contrast to studies with laterally wedged insoles that in both healthy and subjects with OA have had mixed results (Baker et al, 2007;Bennell et al, 2011;Fang et al, 2006;Kakihana et al, 2007;Kutzner et al, 2011;Toda and Tsukimura, 2004). The mechanism by which the external adduction moment is reduced in the VS shoe is not clear.…”
Section: Introductioncontrasting
confidence: 51%
See 2 more Smart Citations
“…The variable stiffness shoe results are in contrast to studies with laterally wedged insoles that in both healthy and subjects with OA have had mixed results (Baker et al, 2007;Bennell et al, 2011;Fang et al, 2006;Kakihana et al, 2007;Kutzner et al, 2011;Toda and Tsukimura, 2004). The mechanism by which the external adduction moment is reduced in the VS shoe is not clear.…”
Section: Introductioncontrasting
confidence: 51%
“…A comparison of the dynamic changes associated with the variable stiffness shoe to kinematic changes in fixed interventions such as lateral wedge shoes might help to explain the difference in the clinical outcome (Erhart et al, 2010) with this shoe relative to the inconsistent results seen with wedged interventions (Kakihana et al, 2007;Toda and Tsukimura, 2004). The primary difference between response to lateral wedge interventions and the variable stiffness shoe is the direction of shift in the COP in combination with the change in the m-l GRF (Fantini Pagani et al, 2011;Kakihana et al, 2007). A lateral shift in the COP and in some instances an increase in the m-l GRF has been reported for the lateral wedge interventions (Fantini Pagani et al, 2011;Hinman et al, 2012;Kakihana et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,[18][19][20] In contrast, no reduction of peak EAMs was found by Schmalz et al 21 when walking with wedged shoes without ankle support. In a study from Kakihana et al, 22 increased EAMs were even reported in about 18% of the patients analyzed.…”
mentioning
confidence: 99%
“…Biomechanical studies have demonstrated a small effect size in reduction of KAM with a valgus knee brace [7][8][9][10] and lateral-wedged insoles. [11][12][13][14] This study is the first to sequentially evaluate the clinical outcomes and gait analyses of different orthotic treatments in Chinese patients with medial compartment osteoarthritis.…”
Section: Discussionmentioning
confidence: 99%